Khaziev Shamil Nikolaevich – Doctor of Law, Associate Professor, Principal Researcher at the Forensic Research Methodology Department - Sh. N. Khaziev (Теория и практика судебной экспертизы, 2024)
When conducting forensic examinations of cultural property, various scientific and technical methods are used, including traceological research methods developed within the framework of forensic science. Traceological research methods are used, in particular, when it is necessary to study knots and loops: analyzing the images of knots and loops in works of painting, graphics, sculpture when resolving disputes regarding the attribution of products; decorative antique objects made using cords, ropes, threads, modern art installations; antique items of historical value. In this case, mainly classification and diagnostic tasks are solved. In some rare cases, identification problems can also be solved using the existing reference and information databases of knots and other fastening methods available to forensic tracers. New possibilities for studying knots and their images using artificial intelligence technologies seem promising.